DETERMINATION OF PROXIMAL THIGH CIRCUMFERENCE IN STUDENTS OF BUKOVINIAN HIGHER EDUCATION INSTITUTIONS DEPENDING ON THE TYPE OF SPORT - Karatieieva, S.Yu.; Slobodian, O.M.; Lavriv, L.P.; Slobodian, K.V.; Muzyka, N.Y. (World of Medicine and Biology, 2022)
As a result of the anthropometric study of 115 students in the first and second years of higher education institutions in Chernivtsi, aged from 16 to 18 years, it was established that basketball players have the greatest length of the proximal circumference of the right thigh – 54.14±2.0 cm, of which 54.06±2.0 cm for boys and 54.08±2.0 cm for girls and volleyball players – 54.00±2.0 cm, of which 53.10±2.0 cm for boys and 53.90±2.0 cm for girls, slightly smaller in football players – 52.27±2.0 cm, of which 51.80±2.0 cm for boys and 52.47±2.0 cm for girls and the smallest tennis player – 48.80±2.0 cm, of which 48.10±2.0 cm for boys and 48.70±2.0 cm for girls. By comparison, volleyball players have the greatest proximal length of the left thigh circumference – 51.77±2.0 cm, of which 51.57±2.0 cm for boys and 51.20±2.0 cm for girls and basketball players – 50.00±2.0 cm, of which 50.20±2.0 cm for boys and 49.80±2.0 cm for girls, slightly smaller in football players – 48.07±2.0 cm, of which 48.05±2.0 cm for boys and 48.02±2.0 cm for girls and the smallest in tennis players – 45.70±2.0 cm, of which 45.45±2.0 cm for boys and 45.30±2.0 cm for girls.
Keywords: students; antoropometric parameters; proximal thigh circumference